Bridging the ‘Next Generation Gap’ – Teacher Educators Enacting the NGSS - Hanuscin, Deborah; Arnone, Kathryn A.; Bautista, Nazan (Innovations in Science Teacher Education, 2016)
Given the shifts required of K-12 education under Next Generation Science Standards (NGSS Lead States, 2013), it is inevitable that change is also required in universities that prepare teachers. While there are currently recommendations for NGSS related professional development for classroom teachers, the literature is less specific when it comes to prospective teachers and their unique needs; however, one consistent call is for the provision of images of the NGSS in action. Prospective teachers’ own K-12 science experiences inform their developing pedagogical knowledge. Given this, understanding what NGSS-aligned instruction might look like in action will be particularly challenging for today’s prospective teachers, whose K-12 science education experiences preceded the NGSS, and who often fail to understand the complexity that underlies teaching (Chval, 2004). A related challenge is that teacher educators’ own classroom teaching experiences preceded this reform as well, and as such they lack experience supporting K-12 students in achieving the performance expectations of the NGSS. Teacher educators can identify existing examples of the NGSS in action using such tools as video cases or create new examples from their own practice. Windshitl et al. (2014) suggest teacher educators take substantive steps to engage in reform by enacting a unit of instruction consistent with the NGSS for K-12 students, perhaps in collaboration with a local teacher. The authors of this paper are all teacher educators who have been acting on the above recommendations to plan and enact instruction that aligns with the NGSS, both with elementary teachers and students. In this manuscript, we highlight examples of NGSS-aligned instructional materials we have created, share insights from enactment of these materials, and articulate the resulting ‘wisdom of practice’ generated throughout this process.